2023
DOI: 10.1039/d3nr01073b
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing formation of high entropy alloy nanoparticles with liquid phase transmission electron microscopy

Abstract: High entropy alloy (HEA) nanoparticles hold promise as active and durable (electro)catalysts. Understanding their formation mechanism will enable rational control over composition and atomic arrangement of multimetallic catalytic surface sites...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…59 Sun et al used systematic solution chemistry to synthesize HEA nanoparticles from a mixture of metal salts and PEG-SH, together with LPTEM to understand the formation mechanism. 7 Interestingly, the HEA nanoparticles formed by solution chemistry here were found to co-exist with stable sub-nanometer clusters and free metal atoms as shown in Fig. 5a.…”
Section: Lptem Investigation Of Chemical Processes During Nanoparticl...mentioning
confidence: 79%
See 3 more Smart Citations
“…59 Sun et al used systematic solution chemistry to synthesize HEA nanoparticles from a mixture of metal salts and PEG-SH, together with LPTEM to understand the formation mechanism. 7 Interestingly, the HEA nanoparticles formed by solution chemistry here were found to co-exist with stable sub-nanometer clusters and free metal atoms as shown in Fig. 5a.…”
Section: Lptem Investigation Of Chemical Processes During Nanoparticl...mentioning
confidence: 79%
“…Recent work by the Jones lab demonstrating the importance of atomically precise metal nanoclusters in seeded nanoparticle synthesis emphasizes the need to consider the molecular structure of intermediate species when developing growth mechanisms for nanoparticles. 130 While studies of bimetallic and HEA nanoparticle revealed sub-nanometer metal clusters in the reaction solution following synthesis, 7,59 these species were below the LPTEM spatial resolution so it could not be verified these clusters were indeed intermediates to the final crystalline nanoparticles. Future research should focus on detecting and characterizing metal cluster reaction intermediates during LPTEM experiments and drawing concrete connections between these intermediates and the nanoparticle formation dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations